The Impact of Loyalty and Work Discipline on Employee Productivity: Evidence from PT Rubber Hock Lie - Bawamenewi, Setia Hati; Sinaga, Irwan Nopian; Butar-Butar, Dwi Fany Fransiska Dewi (Global Insights in Management and Economic Research, 2026)
Purpose of the study: This study investigates the influence of employee loyalty and work discipline on productivity at PT. Rubber Hock Lie Sunggal, an international rubber manufacturing company based in North Sumatra, Indonesia. Materials and methods: A quantitative approach employing saturated sampling was utilized with 50 employees comprising the total workforce. Data collection involved primary sources through structured questionnaires and secondary sources from company documentation. Multiple linear regression analysis was employed to examine the relationships between variables, supplemented by classical assumption tests and hypothesis testing (t-test, F-test, and coefficient of determination). Results: The multiple linear regression equation Y = 5.448 + 0.038X₁ + 0.602X₂ + e demonstrated that both loyalty and work discipline exert positive and significant effects on employee productivity. Partial testing revealed that loyalty significantly influences productivity (tcalculated = 2.269 > ttable = 2.011; p < 0.05), while work discipline demonstrates a stronger effect (tcalculated = 4.185 > ttable = 2.011; p < 0.001). Simultaneous testing yielded Fcalculated = 39.071 > Ftable = 3.20 (p < 0.001), confirming the combined significant effect. The adjusted R² value of 0.608 indicates that 60.8% of productivity variance is explained by loyalty and work discipline, with 39.2% attributed to other factors. Conclusions: Employee loyalty and work discipline significantly enhance productivity in the rubber manufacturing sector. Work discipline demonstrates a more substantial impact compared to loyalty. Organizations should prioritize strengthening disciplinary systems and fostering employee commitment to optimize workforce productivity. These findings contribute to human resource management strategies in manufacturing industries, particularly in developing economies.